2018
DOI: 10.5606/archrheumatol.2018.6562
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Risk Factors in Children Diagnosed With Henoch-Schönlein Purpura

Abstract: Objectives: This study aims to evaluate the frequency of skin, gastrointestinal, joint, and renal involvement in children with Henoch-Schönlein purpura (HSP) and investigate the risk factors for organ/system involvement. Patients and methods: The data of 186 patients (97 boys, 89 girls; mean age 7.4±2.8 years; range 1.5 to 16.5 years) who were followed-up with the diagnosis of HSP in our clinic between October 2011 and December 2013 were evaluated retrospectively. Results: Logistic regression analysis revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
2
14
2
Order By: Relevance
“…It affects both genders equally, and in some studies, there is a slightly male predominance. Male/female ratio was 1.08 in the study of Demircioglu Kilic et al [9] and this number was 1.36 in the cohort of Cakici et al [10]. Age and gender distribution in our study were compatible with the literature and the median age at diagnosis was 7.5 years and the male/female ratio was 1.15.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It affects both genders equally, and in some studies, there is a slightly male predominance. Male/female ratio was 1.08 in the study of Demircioglu Kilic et al [9] and this number was 1.36 in the cohort of Cakici et al [10]. Age and gender distribution in our study were compatible with the literature and the median age at diagnosis was 7.5 years and the male/female ratio was 1.15.…”
Section: Discussionsupporting
confidence: 89%
“…Wang et al [8] searched for risk factors for renal involvement in 2731 children with HSP and stated that age over six years, colder season, late diagnosis (more than eight days between the symptom onset and diagnosis), living in a rural area, recurrence, angioedema, and central nervous system involvement were the significant risk factors for renal involvement. Demircioglu Kilic et al [9] found that the risk of renal involvement was significantly higher in girls, in patients over 10 years, and in patients with elevated CRP. The meta-analysis of Chan et al [21] looked for risk factors for renal involvement in 13 studies (2398 children), and they concluded that male gender, diagnosis >10 years old, GI involvement, arthritis/arthralgia, persistent rash, relapse, elevated antistreptolysin O, low C3, WBC >15.000/mm 3 , and thrombocytes >500.000/mm 3 were associated with renal involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Subcutaneous edema is the other prominent sign of HSP, with an overall frequency of 38.8-51.3%. 7,8,16,17 It an indication for corticosteroid therapy in patients with HSP. 1 In previous studies, the majority of subcutaneous edema was located in the extremities, followed by the head and neck 8 and back.…”
Section: Discussionmentioning
confidence: 99%
“… 1 A recent study of 186 children with IgA vasculitis identified girls, patients aged >10 years, and an increased C-reactive protein level as potential risk factors for IgA nephropathy. 2 Orchitis–Incorrect. IgA vasculitis can involve the male genitalia and induce inflammatory complications such as orchitis and epididymitis.…”
mentioning
confidence: 99%
“… 1 A recent study of 186 children with IgA vasculitis identified girls, patients aged >10 years, and an increased C-reactive protein level as potential risk factors for IgA nephropathy. 2 …”
mentioning
confidence: 99%